When Marian sang [compact disc, unabridged] : the true recital of Marian Anderson : the voice of a century - Ryan, Pam Muñoz (Live Oak Media, 2004)
The inspiring story of Marian Anderson, best known for her historic concert at the Lincoln Memorial in 1939.